Toward an All‐Ceramic Cathode–Electrolyte Interface with Low‐Temperature Pressed NASICON Li1.5Al0.5Ge1.5(PO4)3 Electrolyte. Issue 12 (4th May 2020) - Paolella, Andrea; Zhu, Wen; Bertoni, Giovanni; Perea, Alexis; Demers, Hendrix; Savoie, Sylvio; Girard, Gabriel; Delaporte, Nicolas; Guerfi, Abdelbast; Rumpel, Matthias; Lorrmann, Henning; Demopoulos, George P.; et al.
Abstract: This work shows, for the first time, the critical influence of pressure during the hot sintering stage on the ionic conductivity of the lithium super ionic conductor Li1.5 Al0.5 Ge1.5 (PO4 )3 . A hot press method is developed to obtain high ionic conductivities at the significantly decreased densification temperature of only 650 °C by applying pressure (56 MPa). Considering the possible initiation of undesirable decomposition reactions when cathode materials are annealed at high temperature (typically ≥700 °C), the use of high pressure at 650 °C can significantly limit the formation of degradation by‐products. This study determines the criteria required to optimize the pressure and temperature parameters for enhancing the total ionic conductivity. Finally, this study reports an all solid‐state battery based on a LiFePO4 olivine cathode prepared at 650 °C showing very good Li‐intercalation/deintercalation performance. Good ionic interfacial contact is achieved without using polymer and liquid electrolyte. Abstract : A new hot press method for NASICON Li1.5 Al0.5 Ge1.5 (PO4 )3 is developed to obtain high ionic conductivities at only 650 °C by applying pressure (56 MPa). The use of high pressure at 650 °C can significantly limit the formation of degradation by‐products. This study reports an all solid‐state battery based on a LiFePO4 olivine cathode showing very good Li‐intercalation/deintercalation performance.